PEGEMBANGAN BAHAN AJAR KOMIK FISIKA BERBASIS ANDROID PADA POKOK BAHASAN SUHU DAN KALOR DI MA KELAS XI - Susanti Septiana; Alex Harijanto; Sri Handono Budi Prastowo (JURNAL PEMBELAJARAN FISIKA, 2019)
Abstract Teaching materials are systematically arranged materials or materials that teachers and students use in teaching and learning activities. The teaching material that will be developed by the researcher is comic, this is because students are more interested in teaching materials such as comics. The use of Smarthphone on learning is still not applied to students of MA Al-Misri Rambipuji, this allows researchers to develop physics-based comics teaching materials Android. The Android-based comics have the advantage of attracting students learning, easy to operate, efficient because they do not need paper to print, and are easily carried everywhere. The development of this Android-based physics comic is done on the temperature and heat material because this material is quite difficult to learn because it is abstract that can create different thoughts for the students. The aim of the study was to determine the validity, practicality, and effectiveness of the material of Android-based comic physics on learning. This type of research is development research using NIEVEEN development model which includes, 1), preliminary research, 2) prototyping stage, 3) assessment stage. User validation is done by physics teacher in MA Al-Misri Rambipuji with an average score of 3.64 with a very valid category. The implementation was done by observation by two observer who showed during two meetings had an average score of 3.62 < score ≤ 4.00 meaning that learning can be carried out very well. The average pretests and postest field test in class XI IPA 2 is 24.74 and 64.74 with N-Gain value of 0.54. The analysis of the pretests and Postest values shows moderate criteria which means that Android-based physics comic-teaching materials are included in effective products to improve student learning outcomes. Key word: Comic, Android, Physics